Edukasi Gizi Seimbang Melalui Metode Isi Piringku di SD Nahdlatul Wathan - Anis Rofi Hidayah; Irfiah .; Nurul Lailatul Vitriyah; Hikmatul Lutfi`ah; Werdining Wulan (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2023)
Understanding balanced nutrition in children and toddlers is the key to success in efforts to prevent nutritional problems (Adriani, Kartika, 2011). Nahdlatul Wathon Elementary School is a private elementary school in the Sumberbaru area, Jember Regency which has the habit of eating lunch together with provisions from each home. From routine learning activities, it is known that the habit pattern that is instilled from the family, especially from the role of mother and family, is that healthy and nutritious food is expensive food. Children's understanding of balanced nutrition has an impact on attitudes and behavior in selecting and providing food ingredients and on children's appetite, so providing education to students about the components of balanced nutrition and providing an understanding that nutritious food is not expensive food is a solution to nutritional problems through activities community service through Balanced Nutrition Education activities using the fill my plate method at Nahdlatul Wathan Elementary School. Balanced nutrition education activities are carried out at the stage of brainstorming by asking questions about what food they consume every day. Then ask about their favorite food. The activity then continues by showing a video of the children's song